Changing Business models for Sustainability: Role of drivers and dynamic capabilities in Arctic nature tourism - Sahebalzamani, Samira (UiT The Arctic University of Norway, 2023)
This thesis investigates nature tourism companies, which strive to incorporate sustainability into their business models and change them to be more resilient. For this purpose, it adopts a dynamic perspective on business models by which companies address corporate sustainability which is understood here as a balance among environmental, social, and economic pillars as well as a sustainable competitive advantage. Past studies overlooked the significance of a systematic analysis of drivers and enablers of change as a way to explain how business models are stimulated and changed. Thus, this thesis aims to answer this overall research question: What are the key drivers and dynamic capabilities underlying business model change for sustainability, and how do they give rise to business model changes for sustainability? Four sub-research questions are formulated across three studies: one systematic literature review and two empirical qualitative studies. Article 1 was inspired by the existing literature regarding a prominent knowledge gap in terms of the theorization of business models in tourism research compared to management research. This study resides in a systematic literature review of nature tourism literature about the conceptualization and operationalization of business models with respect to sustainability and innovation. Article 2 follows a qualitative multiple-case study design to comparatively examine five nature tourism companies to explore how their business models are driven to incorporate sustainability aspects. This study differentiates these business models in terms of sustainability integration and underlying drivers to shed light on crucial driving factors in terms of how they can drive various business models to embed sustainability. Article 3 relies on a longitudinal qualitative design to study how nature tourism companies handled the COVID-19 crisis and enhanced their resilience by changing their business models through building dynamic capabilities. To address the temporal aspects of dynamic ...